Recent advances in understanding the role of the hypothalamic circuit during aggression - Falkner, Annegret L.; Lin, Dayu (Frontiers in Systems Neuroscience, 2014)
The hypothalamus was first implicated in the classic “fight or flight” response nearly a century ago, and since then, many important strides have been made in understanding both the circuitry and the neural dynamics underlying the generation of these behaviors. In this review, we will focus specifically on the role of the hypothalamus in aggression, paying particular attention to recent advances in the field that have allowed for functional identification of relevant hypothalamic subnuclei. Recent progress in this field has been aided by the development of new techniques for functional manipulation including optogenetics and pharmacogenetics, as well as advances in technology used for chronic in vivo recordings during complex social behaviors. We will examine the role of the hypothalamus through the complimentary lenses of 1) loss of function studies, including pharmacology and pharmacogenetics, 2) gain of function studies, including specific comparisons between results from classic electrical stimulation studies and more recent work using optogenetics, and 3) neural activity, including both immediate early gene and awake-behaving recordings. Lastly, we will outline current approaches to identifying the precise role of the hypothalamus in promoting aggressive motivation and aggressive action.